2016
DOI: 10.14295/idonline.v10i1.378
|View full text |Cite
|
Sign up to set email alerts
|

Representações da Violência por Professores

Abstract: V Vi io ol le en nc ce e R Re ep pr re es se en nt ta at ti io on ns s b by y T Te ea ac ch he er rs sAbstract: The violence at school has been of concern worldwide. The aim was to analyze violence at school, to from the perception of teachers in the municipality of Simões-IP. Composed the sample, 49 teachers, with 77.6% women and 22.4% men. Of these, 98.0% observed episodes of school violence, the most common type, the equity 28.5%, then 27.2% of physics; 22.8% of neglect and psychological in 21.0% of cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…A study 35 showed that strategies used by teachers to combat school violence include lectures; meetings with the family; dissemination of legislations and the school’s internal regulations; meetings with teachers and the school council, the secretary of education, and the tutelary council; conversations with students involved in violent acts; longer classroom activities; posters; role-playing recreational activities to improve socialization and strict compliance with rules; enforcement of warnings; and expulsion and/or transfer to another school. These measures resulted in lower rates of violence in the investigated schools.…”
Section: Resultsmentioning
confidence: 99%
“…A study 35 showed that strategies used by teachers to combat school violence include lectures; meetings with the family; dissemination of legislations and the school’s internal regulations; meetings with teachers and the school council, the secretary of education, and the tutelary council; conversations with students involved in violent acts; longer classroom activities; posters; role-playing recreational activities to improve socialization and strict compliance with rules; enforcement of warnings; and expulsion and/or transfer to another school. These measures resulted in lower rates of violence in the investigated schools.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter study, most participants were also female (77.6%) and had a partner at the time of the study (59.2%); 6.1% of participants were 20 to 29 years old, 34.7% were 30 to 39, 36.8% were 40 to 49 years old and 22.4% were 49 years or older. 8 …”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Carvalho et al (2016), em um estudo considerando 48 docentes em duas escolas do ensino fundamental do munícipio de Simões (PI), verifi cou-se que a maior parte deles afi rmaram já ter observado violência na escola em que 55,1% relataram ter sido eles próprios vítimas dessa violência. Rocha et al (2012), com dados de 121 profi ssionais de duas escolas, uma particular e uma pública, da cidade de Natal (RN), encontraram que dos 62 funcionários da escola pública e 59 da escola privada amostrados, 43,5% e 25,0% foram vítimas de algum tipo de violência dentro do ambiente escolar, respectivamente.…”
Section: Revisão Bibliográfi Caunclassified
“…Por fi m, foram mantidos apenas os profi ssionais que lecionavam em áreas urbanas, uma vez que o fenômeno estudado é mais persistente nessas áreas (Glaeser;Sacerdote, 1999) e em escolas estaduais e municipais, uma vez que em escolas privadas a violência tende a ser menor (Lowe et al, 2020;Carvalho et al, 2016). O número total de professores após os fi ltros realizados foi de 38.263.…”
Section: Base De Dadosunclassified